2009
DOI: 10.1152/japplphysiol.91614.2008
|View full text |Cite
|
Sign up to set email alerts
|

Axial distribution heterogeneity of nitric oxide airway production in healthy adults

Abstract: Model simulations of nitric oxide (NO) transport considering molecular diffusion showed that the total bronchial NO production needed to reproduce a given exhaled value is deeply influenced by its axial distribution. Experimental data obtained by fibroscopy were available about proximal airway contribution (Silkoff PE, McClean PA, Caramori M, Slutsky AS. Zamel N. Respir Physiol 113: 33-38, 1998), and recent experiments using heliox instead of air gave insight on the peripheral airway production (Shin HW, Condo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 28 publications
(68 reference statements)
1
12
0
Order By: Relevance
“…Important experimental observations by Kerckx and Van Muylem27 have also demonstrated the inhomogeneous distribution of NO production in healthy adults, with the majority of exhaled NO coming from very proximal airways and ‘larger’ peripheral airways of <17 generation, with little contribution from the lung periphery after correcting for axial NO back-diffusion. The response following histamine-induced bronchoconstriction in normal subjects has been studied by Verbanck et al 28 who noted its potential effect to increase convective flow of NO and FeNO at 50 ml/s by a paradoxical decrease in axial back-diffusion of NO.…”
Section: Discussionmentioning
confidence: 99%
“…Important experimental observations by Kerckx and Van Muylem27 have also demonstrated the inhomogeneous distribution of NO production in healthy adults, with the majority of exhaled NO coming from very proximal airways and ‘larger’ peripheral airways of <17 generation, with little contribution from the lung periphery after correcting for axial NO back-diffusion. The response following histamine-induced bronchoconstriction in normal subjects has been studied by Verbanck et al 28 who noted its potential effect to increase convective flow of NO and FeNO at 50 ml/s by a paradoxical decrease in axial back-diffusion of NO.…”
Section: Discussionmentioning
confidence: 99%
“…As the central airway axial diffusion is an important factor determining flow dependency [25] this may indicate that ethanol has a significant axial diffusion and the central airways contribute significantly to total ethanol breath levels. Three subjects with low baseline ethanol levels showed no exhalation flow dependency, suggesting that higher gas levels may be more sensitive flow rate reduction.…”
Section: Discussionmentioning
confidence: 99%
“…decrease or increase) result in immediate FENO changes thus impairing its ability to reflect airway inflammation, especially when peripheral airways are involved [9][10][11][12]16]. This is because the vast majority of NO production is concentrated in small conductive airways [15]. Furthermore, in a model using allergen challenge, it was even shown that during the late inflammatory-phase reaction, the reduction of airway calibre completely counteracted the boosting effect of airway inflammation on FENO levels [12].…”
Section: Discussionmentioning
confidence: 99%
“…This is most likely due to the decrease of available epithelial surface, which impairs NO diffusion from the airway epithelium into the airway lumen [13,14]. The involvement of peripheral airways amplifies this reduction because most NO production is concentrated in small conductive airways [15], which represent the vast majority of the total epithelial surface. Moreover, an acute increase of airway calibre was recently shown to also affect FENO values in a manner depending on the site of bronchodilation (i.e.…”
Section: Introductionmentioning
confidence: 99%